2010
DOI: 10.3109/14767058.2010.490889
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hyperbilirubinemia and G71R mutation of theUGT1A1gene in Turkish patients

Abstract: Our results suggest that G71R mutation of UGT1A1 is not rare; however, an association between G71R mutation and hyperbilirubinemia of unexplained cause has not been shown in Turkish newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 20 publications
(35 reference statements)
0
17
1
Order By: Relevance
“…However, different findings have been reported in Caucasians and Africans (6). Studies in Turkey (19) and the United States (20) found no significant association between 211G>A and neonatal hyperbilirubinemia. In addition, the risk for neonatal hyperbilirubinemia in individuals carrying homozygous 211G>A was higher than in their heterozygous counterparts in this study.…”
Section: Articlesmentioning
confidence: 86%
“…However, different findings have been reported in Caucasians and Africans (6). Studies in Turkey (19) and the United States (20) found no significant association between 211G>A and neonatal hyperbilirubinemia. In addition, the risk for neonatal hyperbilirubinemia in individuals carrying homozygous 211G>A was higher than in their heterozygous counterparts in this study.…”
Section: Articlesmentioning
confidence: 86%
“…This mutation neither influenced the severity of hyperbilirubinemia nor the requirement of phototherapy. The mutant allele frequency did not differ significantly between the two groups and was significantly lower than in the Turkish patients [1] (10.4% vs. 24.3%). Unlike in their cohort, none of our patients were homozygous for the mutant allele and this could be due to the lower frequency of this allele (7.7%) in healthy Indian populations (unpublished data).…”
Section: To the Editormentioning
confidence: 87%
“…We read with interest the report entitled "Neonatal hyperbilirubinemia and G71R mutation of the UGT1A1 gene in Turkish patients" by Narter et al [1]. We have also been studying the genetic risk factors of neonatal hyperbilirubinemia in western India.…”
Section: To the Editormentioning
confidence: 95%
See 1 more Smart Citation
“…By comparing Zhuang and Han patients in the case group or control group, we found that Han patients have a significantly higher frequency of the mutation and A allele, than Zhuang patients do. The finding that A allele frequency in the case group is strikingly higher than that in the control group (regardless of ethnicity) indicates that the UGT1A1 211G>A mutation is associated with the occurrence (Sappal et al, 2002;Kanai et al, 2005;Narter et al, 2011;, whereas studies in most parts of Europe and America showed no correlation of the 211G>A mutation with the occurrence of neonatal unconjugated hyperbilirubinemia in the region (Akaba et al, 1998;Ferraris et al, 2006). (TA)7 insertion mutation refers to insert one more TA sequence based on (TA) 6 so as to transform normal A(TA)6/6TAA mutation into A(TA)6/7TAA hybrid subtype and A(TA)7/7TAA homozygotic type (Fernández Salazar et al, 2000).…”
Section: Discussionmentioning
confidence: 86%